Psikologi Manajemen sebagai Penggerak Inovasi Budaya Organisasi dalam Meningkatkan Efektivitas dan Profitabilitas - Sofyan Sauri; Ulfia Rhodhotul Jannah; Iqbal Alfan Ni’amulloh; Mu’alimin Mu’alimind (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The development of modern organizations demands continuous innovation to maintain effective performance and competitiveness. In this context, the human factor is a crucial element determining organizational success. Management psychology presents itself as an approach that integrates psychological principles with management practices to understand individual behavior within organizations, such as motivation, communication, leadership, and group dynamics. However, various previous studies still tend to discuss psychological aspects partially and have not comprehensively examined the relationship between management psychology, organizational culture innovation, and their impact on organizational effectiveness and profitability. Therefore, this study aims to analyze and synthesize various literature studies on the role of management psychology as a driver of organizational culture innovation in improving organizational effectiveness and performance. This study uses a literature review method by searching for scientific articles through the Google Scholar database with the help of the Publish or Perish application. The keywords used are "management psychology" and "organizational culture innovation." From the initial search process, 10 articles were obtained, then selected based on the inclusion criteria of publication year 2019–2025, topic relevance, and availability of open access, resulting in 5 articles for in-depth analysis. The results of the literature synthesis reveal three main themes: the role of management psychology in human resource development, leadership formation and organizational culture, and increasing organizational effectiveness and innovation. These findings indicate that a management psychology approach contributes to increased motivation, work engagement, and the creation of an innovative organizational culture. Future research is recommended to examine these relationships empirically to gain a more comprehensive understanding of the implementation of management psychology in various organizational contexts.